2013
DOI: 10.17711/sm.0185-3325.2013.036
|View full text |Cite
|
Sign up to set email alerts
|

Psicoterapia de grupo para parejas como modelo de intervención en un instituto de tercer nivel

Abstract: SUMMARYAt the National Institute of Perinatology, a line of clinical psychological research is the study and treatment of patients with couple problems to generate strategies of intervention based on clinical research. ObjectiveTo identify risk indicators in a psychotherapy institutional group process. Material and methodThe qualitative-interpretative method was used. The sessions, in an open group form, were once a week during two hours. Attendance ranged between eight and 12 participants. 35 sessions were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…One of the negative emotions that arises with frequency due to early victimization is anger (Sánchez, Carreño, Watty, & Belmont, 2013). In addition, Milner and Crouch (2004) showed that, among maltreated people, there is the tendency to become more violent than individuals who are not maltreated; this violence was seen with aggression toward peers in general, domestic violence, sexual aggression in adulthood, and even sexual abuse or maltreatment toward their own children.…”
Section: Introductionmentioning
confidence: 99%
“…One of the negative emotions that arises with frequency due to early victimization is anger (Sánchez, Carreño, Watty, & Belmont, 2013). In addition, Milner and Crouch (2004) showed that, among maltreated people, there is the tendency to become more violent than individuals who are not maltreated; this violence was seen with aggression toward peers in general, domestic violence, sexual aggression in adulthood, and even sexual abuse or maltreatment toward their own children.…”
Section: Introductionmentioning
confidence: 99%
“…El trabajo interdisciplinario debe contribuir para que el paciente logre enfrentar de mejor manera su enfermedad y la adherencia a los tratamientos médicos, evitando en la medida de lo posible las complicaciones. En relación a la atención psicológica, ésta debe estructurarse en base a los resultados obtenidos en la investigación, para que el paciente resuelva sus problemas psicológicos o de pareja, si los tiene, con una mayor especificidad (Sánchez-Bravo, Carreño, Watty y Belmont, 2013). Tomando en cuenta que en las instituciones de salud se atiende población que ingresa por tener un padecimiento específico, y que, de manera paralela o de manera reactiva al problema de salud, puede tener problemas psicológi-cos, que es necesario estudiar y atender, y aunque la atención prioritaria es la atención médica, el psicólogo de la salud es pieza fundamental de la atención interdisciplinaria.…”
Section: Hombres Hombresunclassified